Tuning the C1 /C2 Selectivity of Electrochemical CO2 Reduction on Cu-CeO2 Nanorods by Oxidation State Control - Hong, Seungwon (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2022 Wiley-VCH GmbH.